Pengaruh Harga Dan Promosi Terhadap Repurchase Intention Pada Toko Donat Madu Cihanjuang Cabang Cijantra - Zulia Inita; Fadillah Fadillah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstrak. The purpose of this study is to determine the partial and simultaneous effects of price and promotion on repurchase intention at the Cihanjuang Honey Donut Shop, Cijantra Branch. The research method used is quantitative descriptive. The sampling technique used is probability sampling in the form of simple random sampling. The results of the study indicate that price has a positive and significant partial effect, as evidenced by the calculated t-value > t-table (8.877 > 1.984). This was also reinforced by a p-value < Sig.0.05 or (0.000 < 0.05), a correlation value of 0.670, meaning that the two variables have a strong relationship. The coefficient of determination value was 44.8%. Promotion also has a positive and significant partial effect, as evidenced by the t-value > t-table or (11.448 > 1.984). This is also reinforced by a p-value < Sig 0.05 or (0.000 < 0.05), with a correlation value of 0.758, meaning that the two variables have a strong relationship. The coefficient of determination is 57.5%. Price and promotion simultaneously have a significant effect on repurchase intention, as evidenced by the F count value > F table or ((66.438 > 3.09). This is also reinforced by the p value < Sig 0.05 or (0.000 < 0.05). The correlation value of 0.771 means that the independent variable and the dependent variable have a strong relationship. The coefficient of determination or simultaneous contribution value is 59.5%, while the remaining 40.5% is influenced by other factors. Keywords: Price, Promotion, Repurchase Intention.